Matching and credit frictions in the housing market - Essi Eerola; Niku Määttänen (Bank of Finland, 2015)
​We study the interaction of matching and credit frictions in the housing market. In the model, risk-averse households may save or borrow in order to smooth consumption over time and finance owner housing. Prospective sellers and buyers meet randomly and bargain over the price. We analyze how borrowing constraints influence house price determination in the presence of matching frictions. We also show that credit frictions greatly magnify the effects of matching frictions. For instance, in the presence of matching frictions, a moderate tightening of the borrowing constraint increases idiosyncratic price dispersion and the average time-on-the-market substantially.
URN:NBN:fi:bof-201510061415
Keywords: E21; R21; C78; 330